Solid solubility and ionic conductivity of Li₃TaO₄ and related phases - Shari, Syafiqah (2018)
Lithium tantalate solid solution, Li3+5xTa1-xO4 was prepared by conventional solid-state reaction at 925 ⁰C over 48 h. The x-ray diffraction (XRD) analysis confirmed that these materials crystallised in a monoclinic symmetry, space group of C2/c and Z=8, which was similar to the reported International Crystal Diffraction Database (ICDD), 98-006- 7675. β-Li3TaO4 has a rock-salt structure with a cationic order of Li+ : Ta5+ = 3 : 1 over the octahedral sites. The lithium solubility was investigated by varying the lithium content through a proposed formula, Li3+5xTa1-xO4 (0 ≤ x ≤ 0.059). Ac impedance study releaved that Li3TaO4 exhibited the highest conductivity, 3.82 x 10-4 S cm-1 at 600 ºC. The activation energy in the range 0.63 – 0.68 eV were found in these materials. In attempt to investigate the correlation between structural and electrical properties of the Li2O-Ta2O5 systems, various chemical doping was performed. Tetravalent dopant, e.g. Ti4+ was introduced into the host structure with a proposed formula, Li3TixTa1-xO4-x (0.45 ≤ x ≤ 0.75) at same synthesis condition. The formation mechanism involved a one-to-one replacement to Ta5+ cation by Ti4+ cation with the creation of oxygen vacancy for charge compensation. The phase changed from an ordered monoclinic to a disordered cubic phase when x increased from 0 to 0.40. While, a disordered cubic Li3TaO4 phase was observed at x = 0.45-0.75. These materials were refined and fully indexed with a space group of Fm-3m, Z=1 with a slightly smaller lattice parameters, a=b=c, in the range 4.1907(2) – 4.1681(2) Å. The unit cell contraction may be attributed to the replacement of larger Ta5+ (0.64 Å) by a smaller Ti4+ (0.61 Å) at the six-coordination. Li3Ta0.25Ti0.75O3.625 exhibited the highest conductivity among the Ti dopants at all temperatures, i.e. 2.33 x10-4 S cm-1 at 600 ⁰C. The activation energies of these materials were estimated to be 1.16 - 1.32 eV. On the other hand, an attempt was made to replace Nb by Ta using a proposed formula of Li3Ta0.5-xNbxTi0.5O3.775. A complete substitutional solid solution was formed, which was mainly due to the similar chemical characteristics between these pentavalent cations. The lattice parameters a=b=c were determined to be 4.1866(1) – 4.1849(4) Å.Li3Ta0.4Nb0.1Ti0.5O3.75 (x = 0.1) was found to exhibited the highest conductivity, i.e. 1.78 x 10-3 S cm-1 at 600 ⁰C. The activation energies of these materials were estimated to be 1.35 - 1.49 eV. Selected divalent cation dopants were chemically doped into the β-Li3TaO4 monoclinic phase. Both Mg and Zn dopants formed solid solutions with limit up to x = 0.1 only. The chemical formulae of Li3-2xMxTaO4 (M = Mg or Zn) was proposed wherein two Li+ ions were substituted by a divalent M2+ cation. Both doped samples exhibited relatively higher conductivity than that of parent material, β-Li3TaO4. This was probably attributed to the creation of lithium vacancy or well-connected grain. The conductivity values of Li2.8Mg0.1TaO4 and Li2.8Zn0.1TaO4 were determined to be 3.60 x 10-4 S cm-1 and 5.99 x 10-4 S cm-1 at 600 ⁰C, respectively. Their resulted activation energies did not change significantly but remained reasonably low, i.e. 0.55 - 0.58 eV. All the prepared samples appeared to be thermally stable as there are not thermal event detect in both TGA and DTA thermograms. The chemical stoichiometry of these samples was confirmed by ICP-OES, in which comparable values between theoretical and experimental concentrations were obtained. Structural analysis by FT-IR disclosed that several metal-oxygen bonds were found in the wavenumber range 250 - 1000 cm-1. The irregular shaped grains in the range 0.95 – 10.82 μm were also shown by the SEM micrographs. This was further supported by TEM analysis as the results showed some spherical particles with quadrangle edges were found in the samples. In attempts to investigate the possibility of new solid solution formation and to determine the electrical performed of the Li2O-Ta2O5 materials, chemical dopants were performed. These materials showed different solid solution limit and moderate lithium ionic conductivity.